2019
DOI: 10.1002/cplu.201900012
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superhydrophobic Hierarchical Surfaces by Square Pulse Electrodeposition: Copper‐Based Layers on Gold/Silicon (100) Substrates

Abstract: Copper based layers were fabricated on gold/silicon (100) substrates by using square pulse electrodeposition at different deposition temperatures. The predominant crystalline plane on Cu 2 O samples at temperatures higher than 30°C is (111), which is the most hydrophobic facet of Cu 2 O cubic structure. Different crystallite structures such as semivertical leaves, fractal trees, and octahedral pyramids were formed on the surface. These water-repellent samples have hierarchical structures, including octahedral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
(80 reference statements)
2
18
0
Order By: Relevance
“…These conditions can lead to an increase in the copper oxide content of the deposited layer in the higher temperatures. In addition, the reactivity and wetting of the as-prepared copper layers from aqueous solution can also increase the amount of adsorbed oxygen on the layer surface, which can be higher in highly rough-structured layers [28,29,38].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions can lead to an increase in the copper oxide content of the deposited layer in the higher temperatures. In addition, the reactivity and wetting of the as-prepared copper layers from aqueous solution can also increase the amount of adsorbed oxygen on the layer surface, which can be higher in highly rough-structured layers [28,29,38].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional continuous DC electrodeposition, many characteristics of pulse electrodeposition make it especially suitable for the preparation of superhydrophobic coatings. It can not only comprehensively control the crystal growth rate and morphology of deposited materials through parameters such as voltage, current, frequency, and duty cycle but can also rapidly refresh the ions, which is suitable for preparing superhydrophobic films with high surface quality. , However, to our knowledge, few previous studies have been reported to develop a nonfluorinated superhydrophobic metal foam for effective oil/water separation via a facile, nonfluorinated, and economical pulse electrochemical deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well-known that bath temperature changes during the electrodeposition could affect the cathodic overpotential, viscosity of the solution, conductance of ions, and polarity of the electrodes [31][32][33][34][35][36][37][38][39][40][41]. Therefore, both the nucleation and growth could be affected which consequently may change the morphology, grain refinement, coarsening, porosity, and compactness of the layer [31,41].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the cubic Cu2O crystal, the {111} plates have the lowest surface energy and consequently the largest hydrophobicity [46]. Moreover, in the electrodeposition approach, the Cu2O micrometric crystals may be grown in the shape of cubes, octahedral pyramids, triangles, and their truncated structures as well as dendrite structures and fractals [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][47][48][49].…”
Section: Introductionmentioning
confidence: 99%